Optimization of Fine Motor Development: Stimulation of Preschool Children with Playdough Therapy in Kindergarten Level - Sholikhah, Mar'atus; Harmiardillah, Sylvi; Abidah, Sabilatul (Universitas Muhammadiyah Lamongan, 2025)
Introduction: Development is the increase in the ability (skill) of the structure and function of the child's body which is more complex as a result of the body maturation process. Children of this age are expected to have mastered several skills that require fine motor skills. The aims of this study was to analyze the effect of playdough therapy on fine motor development in preschool students. Methods: The study used a descriptive case study design. The population was one class, and the sample was taken by simple random sampling according to the inclusion and exclusion criteria. The respondents were three Kindergarten students in October 2024. The instrument used was a DDTS to assess how much stimulation affects a child’s fine motor development. Data was analyzed with descriptive analytics. Results: Before the implementation of playdough therapy, there were 1-2 respondents who could not imitate until after the implementation all respondents could do everything. After 5 days of therapy, all students were able to play with playdough on several items, include imitate vertical lines, imitate circular, imitate a quadrilateral, imitate a triangle, and imitate diagonal lines. Conclusion: The implementation of playdough therapy for 5 days with a duration of 10 minutes to 3 kindergarten children showed fine motor development. Fine motor development education needs to be conveyed to parents, so that they can provide stimulation at home. Keywords: Fine-motor development, Playdough, Preschool students, Stimulation